1991
DOI: 10.1088/0953-4075/24/10/009
|View full text |Cite
|
Sign up to set email alerts
|

L X-ray production cross sections of 59<or=Z<or=70 elements by proton and4He ion impact

Abstract: L x-ray line production cross sections for proton and 'He ion bombardment of elements with atomic number Z ranging from 59 to 70 have been measured in the energy range 0.25-1.80 MeV far protons and 0.40-1.80 MeV far 4He ions. An overall good agreement with the few existing data has been observed. The linear dependence on Z of the logarithm of the cross sections has been confirmed also in this region. The agreement of the measured data with the predictions of a modified ECPSSR model, suggested by us and based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…The linear dependence on Z of the logarithm of both theoretical and experimental ionization cross section values can be clearly pointed out. This observation agrees with other observations seen in the literature (Vigilante et al 1991).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The linear dependence on Z of the logarithm of both theoretical and experimental ionization cross section values can be clearly pointed out. This observation agrees with other observations seen in the literature (Vigilante et al 1991).…”
Section: Resultssupporting
confidence: 94%
“…In making the comparison between theory and experiment for the L 1 -subshell, the ECPSSR theory seems to overestimate the experimental values for all values of Z. This agrees somewhat with other observations seen in the literature (Hallak 1997a, b, Bogdanovic et al 1996, Sarkar et al 1995, Orlic 1994, De Cesare et al 1994, McNeir et al 1994, Semaniak et al 1993, Cai et al 1992, Sarkadi and Mukoyama 1991, Vigilante et al 1991 at the above-mentioned energy. For the L 2 -subshell, the data shown in figure 1 indicate the same exponential functional dependence for both theory and experiment, but the ECPSSR theory now underestimates the experiment.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The theory seems to overestimate the experimental data for all elements examined. This result is in agreement with our previous work 1 -3 and that of Vigilante et al 12 for protons and 4 He ions, Mehta et al 21 for carbon ions and Bogdanovic et al 22 for 16 O ions. They all found that the logarithm of the crosssections or L-subshell intensity ratios varies linearly with the atomic number.…”
Section: Data Analysis Proceduressupporting
confidence: 93%
“…This disagreement came originally from an underestimation of the L b and L c X-ray production cross sections. The compilation of data on 4 He-induced X-ray emission is still incomplete as can be seen in [9][10][11]. L shell X-ray production cross sections are lacking for L a , L b and L c lines at energies above 1.8 MeV for Pt and Bi.…”
Section: Introductionmentioning
confidence: 99%